Basic heart examination: feasibility study of first‐trimester systematic simplified fetal echocardiography. (February 2017) - Quarello, E.; Lafouge, A.; Fries, N.; Salomon, L. J.; ,
Abstract: Objective: First‐trimester fetal cardiac screening examinations in low‐risk populations should not have to meet the specifications required for high‐risk populations. Our aim was to evaluate a simplified fetal echocardiographic ('basic heart') examination for early detection of severe congenital heart defects in a low‐risk population. Methods: This was a first‐trimester national 'flash study', performed over a 2‐week period. Each observer was requested to perform simplified echocardiography without modifying the time and methods deemed necessary for the routine first‐trimester ultrasound examination, in fetuses with crown–rump length between 45 and 84 mm. This basic heart assessment used targeted cross‐sections of the four‐chamber view (4CV) and of the three vessels and trachea (3VT) view, using color and/or directional power Doppler. All examinations were then reviewed offline and scored for quality by a qualified expert. Results: Sixty observers performed a total of 597 first‐trimester ultrasound examinations, each performing an average of 10 (range, 1–26) procedures. Examinations were conducted transabdominally (79%; 472/597), transvaginally (3%; 17/597) or both (18%; 108/597). In 8% (45/597) of cases, the fetal back was anterior, in 18% (108/597) it was on the left side, in 63% (377/597) it was posterior and in 11% (67/597) it was on the right side. It became clear during scoring by the expert that, unlike the Herman quality score for nuchal translucency measurement, it was difficult to assess the quality of these images without taking into account normality of the heart itself. Analysis of scores showed that the 4CV was obtained successfully and was deemed normal in 86% (512/597) of the patients, in 7% (41/597) it was deemed technically infeasible and in 7% (44/597) it was deemed feasible but atypical, which may have been due to the presence of an abnormality or to poor quality of the image. The 3VT view was obtained successfully and was normal in 79% (472/597) of the patients, in 13% (78/597) it was technically infeasible and in 8% (47/597) it was deemed feasible but atypical. Both the 4CV and the 3VT view were obtained successfully and were normal in 73% (435/597) of patients. Conclusion: It is possible for a trained operator to perform simplified fetal echocardiography during the routine first‐trimester ultrasound examination in a low‐risk population. In most cases, our basic heart examination can be used to reassure parents or identify potential problems to be clarified as early as possible in the second trimester. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.